CORPORATE VENTURE CAPITAL AND STARTUP FINANCING: A COMPARATIVE ANALYSIS - Ubarhande, Kavita; Vanarse, Shubhangi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Corporate Venture Capital (CVC) has become a significant source of financing for startups, often seen as an alternative to conventional venture capital (VC) funding. With an emphasis on funding amount, strategic assistance, and long-term effects, this study compares corporate venture capital (CVC) with traditional venture capital (VC) in terms of startup financing. This research uses quantitative analysis of responses from 150 startup founders, investors, and industry experts to explain the influence of different funding strategies on entrepreneurial success. The results underscore the benefits and drawbacks of corporate venture capital (CVC) relative to traditional venture capital (VC) in promoting innovation, growing firms, and meeting financial and strategic requirements.